2017
DOI: 10.1002/ps.4625
|View full text |Cite
|
Sign up to set email alerts
|

Lack of transgene and glyphosate effects on yield, and mineral and amino acid content of glyphosate‐resistant soybean

Abstract: Neither glyphosate nor the GR transgene affect the content of the minerals measured in leaves and seed, harvested seed amino acid composition, or yield of GR soybean. Furthermore, soils with a legacy of GR crops have no effects on these parameters in soybean. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…After considering this lack of influence of glyphosate or the GR trait, a US National Academy of Science study suggested that more research should be carried out in controlled environments with appropriate controls to determine if yields are affected by glyphosate or the GR transgene . Such studies carried out recently have found no effects of glyphosate use on GRCs or the GR transgene on crop yield …”
Section: Detractorsmentioning
confidence: 99%
See 2 more Smart Citations
“…After considering this lack of influence of glyphosate or the GR trait, a US National Academy of Science study suggested that more research should be carried out in controlled environments with appropriate controls to determine if yields are affected by glyphosate or the GR transgene . Such studies carried out recently have found no effects of glyphosate use on GRCs or the GR transgene on crop yield …”
Section: Detractorsmentioning
confidence: 99%
“…The most publicized claims of problems with GRCs have centered around plant disease, mineral nutrition, yields, and glyphosate toxicology. Two of these topics, mineral nutrition and plant disease as affected by glyphosate, are dealt with in other papers in this special issue of Pest Management Science . Briefly, despite a few highly publicized papers indicating that glyphosate alters plant mineral nutrition in GRCs and that this and other GRC characteristics result in increased fungal pathogen infestation of GRCs, the preponderance of peer‐reviewed literature does not support these theories …”
Section: Detractorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The massive use of glyphosate, totaling 852 million kg globally by 2014 (Benbrook, 2016), which directly or indirectly will expose non-target biodiversity in terrestrial, soil and aquatic communities (Venter and Bøhn, 2016), represent a major source of environmental pollution. In addition, glyphosate is shown to accumulate in (i) soils that have a history of glyphosate use (Duke et al, 2017), and (ii) in HT soybeans (Bøhn et al, 2014), more when the plant is sprayed later in the season (Duke et al, 2003). This will bring glyphosate residues into the global food and feed chains (Bøhn et al, 2014).…”
Section: Herbicide Tolerant Crops and Weed Resistance Evolutionmentioning
confidence: 99%
“…The remarkable success of GR sugar beets in the US is reviewed for the first time . Additional evidence is provided in a research paper to support the view that neither glyphosate nor the glyphosate resistance gene affects amino acid or mineral content of GR soybeans . Sammons et al report the effects of the double mutation TIPS EPSPS transgene that is used in some GR crops on Arabidopsis thaliana , and Firdous et al identify and characterize a new GR EPSPS from a soil microbe, a possible new transgene.…”
mentioning
confidence: 99%